Heart disease and COVID-19 - Das, Prabir Kumar; Rahman, Fazlur (University Heart Journal, 2020)
Background:Many patients with coronavirus disease 2019(COVID-19) have pre-existing heart disease or develop various cardiac complications during the disease. Understanding the relationship between heart disease and COVID-19 is necessary for optimum management of such condition. Methods: Literature search done by using Google search engines and PubMed. Results: Heart involvement occurs in approximately 8-12% of all patients. Acute cardiac injury, as evident by a significant cardiac troponin elevation is the commonest abnormality. Myocarditis, type II myocardial infarction, heart failure, arrhythmia are other cardiac menifestations that are less common. Pre-existing heart disease and/or involvement of the heart by COVID-19 carries worse prognosis. Conclusion: Most of the reports currently available describes cardiac menifestations briefly. Further study may reveal more clearly the various aspects of cardiac menifestations in COVID-19 patients. University Heart Journal Vol. 17, No. 1, Jan 2021; 60-65